A Note on Conscience and Authority - Aldana Valenzuela, Ricardo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
This paper addresses the relationship between conscience and authority, first within the standpoint of conscience, that stems since its awakening, with an ever-greater foundation than herself, and following this, from the standpoint of authority, whose purpose is to serve the conscience and freedom. Conscience and authority, then are reciprocally implied. The paper also deals with the abuse of authority over the conscience, following on the unjustified pretense of the conscience over authority. Finally, it is exposed the importance the concern in the life of John Henry Newman and the principles for a solution he offerred.
Keywords: being; gift; duty; foundation; freedom; abuses; Newman; education